Day 1 Extracranial Internal Carotid Artery Patency Is Associated With Good Outcome After Mechanical Thrombectomy for Tandem Occlusion. Issue 10 (October 2018) - Bricout, Nicolas; Personnic, Thomas; Ferrigno, Marc; Labreuche, Julien; Estrade, Laurent; Bretzner, Martin; Leclerc, Xavier; Cordonnier, Charlotte; Boulouis, Grégoire; Henon, Hilde
Abstract : Background and Purpose—: Optimal management of the extracranial occlusive component remains controversial in patients with acute ischemic stroke by tandem occlusion treated with mechanical thrombectomy. We investigated the association between extracranial internal carotid artery (ICA) patency at day 1 and the clinical outcome after mechanical thrombectomy. Methods—: Consecutive patients with acute ischemic stroke with tandem occlusion were identified from a hospital-based prospective registry from 2011 to 2017. Baseline characteristics, angiographic outcomes, and day 1 ICA patency assessed by MR angiography were analyzed with regard to their associations with 3-month modified Rankin Scale scores. Favorable outcome was defined as a modified Rankin Scale score of 0 to 2 at 3 months. Results—: Of 594 patients with acute ischemic stroke treated with mechanical thrombectomy during the study period, 83 met inclusion criteria. Successful recanalization (modified Thrombolysis in Cerebral Infarction, 2b/3) was achieved in 61.5%. Extracranial ICA was patent in 37 of 83 patients (44.6%) at day 1, more frequently in those with prior intravenous thrombolysis ( P =0.035) or with cervical revascularization procedure (balloon angioplasty or stenting, P =0.034). Favorable 3-month functional outcome was more frequent in patients with patent extracranial ICA at day 1 (adjusted odds ratio, 4.72; 95% CI, 1.76–13.34; P =0.003) independent of intracranial recanalization success. Conclusions—: Day 1 stable extracranial ICA patency is associated with better clinical outcome in patients with acute ischemic stroke with tandem occlusions. Randomized studies are needed. Abstract : Supplemental Digital Content is available in the text.